STUDI PERBANDINGAN KUAT TEKAN BETON DENGAN AGREGAT KASAR MENGGUNAKAN METODE SNI DAN METODE MAXIMUM DENSITY - Muhammad Shalahuddin (Jurnal Teknik Sipil, 2016)
Abstract : Variations aggregate gradation in the mixed concrete greatly affect the characteristicsof the concrete. Concrete with dense and continuous gradation is expected to reduce the levels ofair and increases the unit weight of concrete and add to the strength of concrete.Concrete mixturewas planned SNI method with 25 MPa compressive strength with cement and water factorvariation and 15 sample units. To compare the methods of concrete mixtures with the maximumdensity with variation of water cement factor and sample cube 15 units.Compressive strength ofmaximum density method 26 Mpa and SNI method 23,8 Mpa. The compressive strengthmaksimum density method is higher 9.24 % than SNI method, it is also supported by the results ofconcrete weight 8117 kg at maximum density method and 8068 kg at SNI method. Slump withmaximum density method and SNI method shows the same value, then the level of work abilityis also the same.Keywords: Maximum Density, SNI, compressive strength of Concrete.